Study of serum uric acid level as a prognostic marker in acute ST elevation myocardial infarction patients - Behera, Suresh Kumar; Samal, Akshaya Kumar (International Journal of Advances in Medicine, 2018)
Background: The study was conducted to correlate serum uric acid levels with Killip class i.e. severity of heart failure in patients with ST elevation myocardial infarction (STEMI) and to assess any influence of serum uric acid levels on in-hospital mortality in STEMI patients. Methods: Authors evaluated 250 consecutive (STEMI) patients who were hospitalized within 24 hours of symptom onset from September 2015 to august 2017. Detailed history, physical examination was done as per a structured proforma and necessary laboratory investigations were done. Results: There was significant difference in mean serum uric acid level between diabetic and non-diabetic population. There was significant difference in mean uric acid level between hypertensive and non-hypertensive population. Serum uric acid level was high among STEMI patients with Killip class III and IV and low among patients with Killip class I and II. The higher the uric acid level was, the higher was the percentage of mortality during 5 days hospital course. Conclusions: Patients of higher Killip class had higher levels of serum uric acid as compared to patients of lower Killip class. Serum uric acid level when combined with Killip class is a good predictor of severity of heart failure and short-term mortality after STEMI.